MODELING FRAMING SYSTEMSCHODO THEIR ADAPTATION TO RESIDENTIAL BUILDINGS - , С. М. (Municipal economy of cities. Series: «Economy science», 2013)
We investigate graph-analytic model of interspecific frame s.1.020-1/87 to adapt it for residential buildings with a modern level of comfort and class kapitalnosti. Ways of modifying the frame, providing space-variance planning options residential and commercial buildings of different heights.